2017
DOI: 10.3748/wjg.v23.i33.6137
|View full text |Cite
|
Sign up to set email alerts
|

Patients with inflammatory bowel disease have increased risk of autoimmune and inflammatory diseases

Abstract: AIMTo investigate whether immune mediated diseases (IMD) are more frequent in patients with inflammatory bowel disease (IBD).METHODSIn this population based registry study, a total of 47325 patients with IBD were alive and registered in the Danish National Patient Registry on December 16, 2013. Controls were randomly selected from the Danish Civil Registration System (CRS) and matched for sex, age, and municipality. We used ICD 10 codes to identify the diagnoses of the included patients. The IBD population was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
132
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(147 citation statements)
references
References 80 publications
8
132
0
7
Order By: Relevance
“…A number of case reports and clinical studies have reported new onset IBD with the initiation of anti‐IL‐17 agents . It is well known that patients with immune‐mediated diseases are at increased risk of developing or having a history of IBD . Therefore, comparing patients who received anti‐IL‐17 agents and those receiving placebo therapies in RCTs can help determine whether the risk of new onset IBD is attributed to anti‐IL‐17 agents or it is simply the natural evolution of IBD in susceptible patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of case reports and clinical studies have reported new onset IBD with the initiation of anti‐IL‐17 agents . It is well known that patients with immune‐mediated diseases are at increased risk of developing or having a history of IBD . Therefore, comparing patients who received anti‐IL‐17 agents and those receiving placebo therapies in RCTs can help determine whether the risk of new onset IBD is attributed to anti‐IL‐17 agents or it is simply the natural evolution of IBD in susceptible patients.…”
Section: Discussionmentioning
confidence: 99%
“…PlaceboAnti-IL-17 drug Brodalumab; P = 1.00, Heterogeneity; I 2 = 0 %, Q = 0, P = 1.00 lxekizumab; P = 0.20, Heterogeneity; I 2 = 0 %, Q = 0.15, P = 1.00 Secukinumab; P = 0.70, Heterogeneity; I 2 = 0 %, Q = 1.33, P = 1.00 Overall; P = 0.35, heterogeneity; I 2 = 0 %, Q = 2.41, P = 1.00 of developing IBD in patients treated with anti-IL-17 agents compared to placebo.A number of case reports and clinical studies have reported new onset IBD with the initiation of anti-IL-17 agents 15,16. It is well known that patients with immune-mediated diseases are at increased risk of developing or having a history of IBD [42][43][44]. Therefore, comparing patients who received anti-IL-17 agents and those receiving placebo therapies in RCTs can help determine whether the risk of new onset IBD is attributed to anti-IL-17 agents or it is simply the natural evolution of IBD in susceptible patients.…”
mentioning
confidence: 99%
“…However, the prevalence of CeD in cohorts of patients with IBD remains unclear. In the study performed on a registry including 47,325 Danish patients with IBD immune system-related disorders, including CeD, were found to be more common, likely because of overlapping between signaling and cell activation pathways (21). An Italian study supports this theory, but their cohort of patients with UC is very small (n = 27) (22).…”
Section: Is Celiac Disease Really Associated With Inflammatory Bowel mentioning
confidence: 99%
“…Gut microbiota is involved in regulating both Th1 and Th2 immune response. Thus, in patients with IBD the gut microbiota has been shown to be of less diversity, an altered microbial metabolite profile with reduced number of bacteria compared to healthy individuals has been demonstrated [79]. A similar etiology is believed to exist in rheumatoid arthritis, ankylosing spondylitis, multiple sclerosis, type 1 diabetes mellitus (T1DM), and celiac disease [80].…”
Section: Microbiota and Immunity -Allergy And Autoimmune Diseasesmentioning
confidence: 99%